2014
DOI: 10.1007/s11060-013-1349-2
|View full text |Cite
|
Sign up to set email alerts
|

CUL4A is overexpressed in human pituitary adenomas and regulates pituitary tumor cell proliferation

Abstract: Cullin 4A (CUL4A) encodes a core subunit of an E3 ubiquitin ligase that targets proteins for ubiquitin-mediated degradation, and aberrant expression of the CUL4A is found in many tumor types. However, its roles and clinicopathologic significance in pituitary adenomas are not clear. The aim of this study was to investigate the possible role of CUL4A in pituitary tumorigenesis. Immunohistochemistry was used to examine CUL4A expression in human normal pituitaries and pituitary tumors with respect to various clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…In the search for markers of PA aggressiveness, many biological molecules have been investigated, including growth factors and their receptors, angiogenic factors, matrix metalloproteinases, miRNAs, and many others, but none of them has gained wide acceptance and use (9,17,18,19,47). Ki-67 LIO3% has been proposed by the 2004 WHO classification as a marker of atypical adenomas, along with the presence of mitoses and p53 nuclear labeling, although its effectiveness is far from being universally accepted (3,6,9,12,13,15,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…In the search for markers of PA aggressiveness, many biological molecules have been investigated, including growth factors and their receptors, angiogenic factors, matrix metalloproteinases, miRNAs, and many others, but none of them has gained wide acceptance and use (9,17,18,19,47). Ki-67 LIO3% has been proposed by the 2004 WHO classification as a marker of atypical adenomas, along with the presence of mitoses and p53 nuclear labeling, although its effectiveness is far from being universally accepted (3,6,9,12,13,15,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple molecular dysfunctions are associated with GBM formation and growth, such as EGFR, TGF-b1, VEGF, p53, pRb, p21, p27, p16, p19, and telomerase [20][21][22][23][24][25][26]. Considerable effort has been made to determine the underlying mechanisms of gliomagenesis, but an effective therapy has not been established and patients diagnosed with GBM have a median survival of only 12-15 months [27,28]. In the present manuscript, we identified KDM5B as a candidate target gene for glioma growth.…”
Section: Discussionmentioning
confidence: 99%
“…27 Mechanistically, CUL4A modulates the expression of p53, p27, and Bcl-2 in pituitary tumor cells. 10,11 Similarly, we found that knockdown of CUL4A downregulated the expression of MMP-2 and upregulated the expression of p27 and p53 in OS cells, suggesting that CUL4A might be involved in the development of OS cells via regulation of the expression of p27, p53, and MMP-2.…”
Section: Discussionmentioning
confidence: 62%
“…[10][11][12] In addition, CUL4A induces tumorigenesis of skin cancer by inhibition of DNA repair and accelerating S phase entry, 13 and results in inactivation of RASSF1A and promoting cell cycle progression, 14 suggesting that CUL4A may play a critical role in regulation of some biological processes. 15 Up to now, few studies report the link between CUL4A expression and OS.…”
Section: Introductionmentioning
confidence: 99%